SAT-550 Changes in Albuminuria Precede Dietary Sodium-Dependent Changes in BP During Aging - a Longitudinal Study - Katayama, Isis Akemi (J Endocr Soc, 2020)
Background: Hypertension (HT) is a well-established independent risk factor for adverse cardiovascular and renal (CVR) outcomes and a high salt (HS) diet is the main cause for high blood pressure (BP). Despite extensive research focusing on HT, surprisingly there are no longitudinal studies assessing the long-term effects of HS. Aims: This study aimed (1) to evaluate the timing of onset for changes in CVR health during long-term sodium loading and (2) to assess whether salt restriction can prevent these effects. Methods: C57BL/6 mice were randomized to HS, moderate (NS) or low (LS) salt diet and followed longitudinally for 50 weeks (wks). BP, urinary albumin/creatinine ratio (AC), plasma aldosterone (PA) and renin activity (PRA) were assessed monthly. At the end of the study, renal artery resistance and left ventricular (LV) parameters were measured by ultrasound and echocardiogram. Renal AT1 expression (Western Blot) and activity (IHQ) were quantified. Results: At the beginning of the study, there were no differences in BP and AC between the three dietary groups. Relative to wk 1, BP (mmHg) in the HS group was higher in wk 21 (131±1.7 vs. 115±3.0, p= 0.05). Sodium restriction delayed this increase: SBP was higher in wk 41 in the NS group compared to the wk 1 (128±3.4 vs. 115±6.4, p= 0.05) but did not reach significance in the LS group until the end of the study. Similarly, relative to wk 1, AC (µg/mg) only in the HS group reached significantly higher levels in wk 17 (44±4.2, p<0.05). Again, sodium restriction delayed the occurrence of renal damage. AC reached significance in wks 25 and 41 for NS and LS (35±1.1 and 42±2.6 respectively, p<0.05 vs. baseline). Interestingly, the changes in AC always preceded the changes in BP, irrespective of diet. PA and PRA were appropriately activated by dietary salt restriction and suppressed by aging. The aging-induced suppression appeared stronger for PA than for PRA in the HS group only. Long-term sodium loading (HS) induced increased renal resistance, which was prevented in the LS but not in the NS group. Relative to HS, the LV mass index and cardiac output were lower in the NS and LS groups (p<0.05). LV volume indices and ejection fraction did not differ between groups. Renal AT1 protein expression and activation status (IHQ) were decreased in the sodium restricted group. Conclusions: Our study showed that long-term exposure to HS induced a progressive increase in BP and AC in mice. Importantly, these changes were delayed by long-term reduction in sodium intake. Interestingly, changes in AC preceded those in BP, irrespective of diet. Cardiac parameters suggest a sodium-induced eccentric cardiac hypertrophy in the older age, which was prevented by sodium restriction. One possible mechanism behind these effects is the overactivation of the AT1 receptor pathway.